2016
DOI: 10.1016/j.biortech.2015.08.084
|View full text |Cite
|
Sign up to set email alerts
|

Improving biogas production from microalgae by enzymatic pretreatment

Abstract: Please cite this article as: Passos, F., Hom-Diaz, A., Blanquez, P., Vicent, T., Ferrer, I., Improving biogas production from microalgae by enzymatic pretreatment, Bioresource Technology (2015), doi: http://dx.doi.org/10. 1016/ j.biortech.2015.08.084 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…This is common for complex cultures, such as the one of the present study, composed by several microalgae species, bacteria and other microorganisms with different cell wall compositions. The results are in accordance with previous studies, where microalgae methane yield was increased when non-specific enzymes were added confirming the synergistic effect [10,12,13].…”
Section: Biogas Production In Bmp Testsupporting
confidence: 92%
See 1 more Smart Citation
“…This is common for complex cultures, such as the one of the present study, composed by several microalgae species, bacteria and other microorganisms with different cell wall compositions. The results are in accordance with previous studies, where microalgae methane yield was increased when non-specific enzymes were added confirming the synergistic effect [10,12,13].…”
Section: Biogas Production In Bmp Testsupporting
confidence: 92%
“…The most commonly used enzymes for microalgae pretreatment are commercial α-amylases, amyglucosidases, cellulases, xylanases, lipases or proteases [10,11]. Furthermore, it has been shown that using a mixture of commercial enzymes, the methane yield was higher than using a single enzyme specific for one substrate [10,12]. Regarding the use of crude fungal enzymes, those from Aspergillus lentullus were particularly effective at improving microalgae anaerobic biodegradability [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, both approaches perform as expected. Trials with standalone pretreatment with cellulases and other polysaccharases for 6 h–7 days at 37–50 °C [3, 1618] have shown more mixed results, ranging from no effect at all on rate and yield [3] to increased yield only [16, 17], increased rate only [18] or a combination of both increased yield and rate at selected time points [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Microalgal biomass has ample post-application potential; it could be a source of highvalue products for use as biofuels and bioproducts (Mennaa et al, 2015;Molinuevo-Salces et al, 2016;Passos et al, 2015;Zhang et al, 2016).…”
mentioning
confidence: 99%